2020
DOI: 10.1016/j.molliq.2020.114493
|View full text |Cite
|
Sign up to set email alerts
|

Promising terpenes as SARS-CoV-2 spike receptor-binding domain (RBD) attachment inhibitors to the human ACE2 receptor: Integrated computational approach

Abstract: The spike protein receptor binding domain (S-RBD) is a necessary corona-viral protein for binding and entry of coronaviruses (COVs) into the host cells. Hence, it has emerged as an attractive antiviral drug target. Therefore, present study was aimed to target severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) S-RBD with novel bioactive compounds to retrieve potential candidates that could serve as anti-coronavirus disease 2019 (COVID-19) drugs. In this paper, computational approaches were employed, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 70 publications
(89 reference statements)
4
62
0
1
Order By: Relevance
“…Generally, the unbound RBD structures had the highest RMSD values ( Figure 6 a). A recent molecular dynamics study of RBD and terpene compounds reported a similar RMSD range of 0.08 and 0.25 nm [ 99 ].…”
Section: Resultsmentioning
confidence: 94%
“…Generally, the unbound RBD structures had the highest RMSD values ( Figure 6 a). A recent molecular dynamics study of RBD and terpene compounds reported a similar RMSD range of 0.08 and 0.25 nm [ 99 ].…”
Section: Resultsmentioning
confidence: 94%
“…This discovery is of great significance for pharmacological and pharmacodynamic studies of drug combinations. Phytochemicals, such as flavonoids, isatins, and terpenoids, which exert recognized curative effects against SARS-CoV-2 infection, might be used in many people owing to their safety, low pharmacological side effects and availability [ 121 , 122 ]. However, the targets and mechanisms of action of several drug candidates remain unclear.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…S-protein is additionally focused with the most ordinarily discovered phytochemicals, where Kaempferol, Quercetin, and Fisetin had been appeared to bind and block the RBD which is validated utilizing molecular docking and MD reenactments [ 45 ]. Terpenes from plant sources like Trevesia Palmata , Aralia Dasyphylla and Glycyrrhiza glabra have shown the potentials to block and mask the RBD using computational methods is reported [ 46 ]. In another study, Epigallocatechingallate, Curcumin, Apigenin and Chrysophanol were identified to be potential hits possessing ability to serve as RBD blockers [ 47 ].…”
Section: Discussionmentioning
confidence: 99%